2475 Graphic Novel and the Representation of the 1932 Siamese Revolution in Contemporary Thai Society - Sarunyou Thepsongkraow (Journal of Integrative and Innovative Humanities, 2024)
This article aims to study the graphic novel “2475 Graphic Novel” (“2475: GhostWriter of Siam” in Thai) by Thanis Wirasakdiwong and Podcharakrit To-im, as a creative work that represents the 1932 Siamese Revolution in contemporary Thai society and connects it with the political activities of the new generation. The study found that the phenomenon of reviving and destroying memories of the People’s Party (Khana Ratsadon in Thai), especially after the 2014 coup, as well as the youth movement calling for democracy throughout 2020, has brought the story of the People’s Party back to life again through a variety of media presentations to respond to the visual culture in line with the political movements of the new generation. The book “2475 Graphic Novel” presents the stories of common people who participated in the Siamese Revolution together with the People’s Party. The authors interpreted the People’s Party in a new way and presented the image of the Siamese Revolution in a way that is in line with the contemporary era, starting from the roles of women in the Siamese Revolution, the problems of inequality in Thai society before the 1932 Revolution, and the perspectives of the People’s Party and the ruling class of the old regime. In addition, the book aims to fill readers with hope and encourage new generations who want to change Thai society for the better.